2017
DOI: 10.1108/bfj-06-2016-0276
|View full text |Cite
|
Sign up to set email alerts
|

Study on FT-MIR spectra of ghee (anhydrous milk fat)

Abstract: Purpose Ghee, anhydrous milk fat, is chemically highly complex in nature. The authentication and characterization of edible fats and oils by routine chemical methods are highly laborious and time consuming. Fourier transform-mid-infrared (FT-MIR) spectroscopy has emerged as a predominant analytical tool in the study of edible fats/oils. However, sufficient attention has not been paid so far to spectral characterization of milk fat obtained from cow and buffalo milk. The purpose of this paper is to fill this vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This indicated that the used solvents were inert to the milk fat and did not result into any chemical alterations. The observed differences in the position of absorption peak could be attributed to the difference in the composition of fatty acids present in these samples, that is variation in the number of carbon atoms in the chain length, number of double or triple bonds (level of unsaturation), position and arrangement of these bonds (Lerma‐García et al., 2010; Antony et al., 2017). Further, it could be seen that all the samples exhibited small absorbance peaks in the 2400–2000 cm −1 region, which indicates about the presence residues of thermally denatured protein in these samples.…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that the used solvents were inert to the milk fat and did not result into any chemical alterations. The observed differences in the position of absorption peak could be attributed to the difference in the composition of fatty acids present in these samples, that is variation in the number of carbon atoms in the chain length, number of double or triple bonds (level of unsaturation), position and arrangement of these bonds (Lerma‐García et al., 2010; Antony et al., 2017). Further, it could be seen that all the samples exhibited small absorbance peaks in the 2400–2000 cm −1 region, which indicates about the presence residues of thermally denatured protein in these samples.…”
Section: Resultsmentioning
confidence: 99%
“…A sharp and strong band recorded at 1161 cm −1 can be assigned to the C–O bond stretching vibration in HC–O–(C=O) of the ester group. However, the weak vibrational signal at 1116 cm −1 corresponded to the C–O stretching in O–C–C of the ester [ 49 ]. A medium-strong vibrational signal corresponding to the stretching of C–C bonds present in the hydrocarbon chains was noticed at 1097 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…A medium-strong vibrational signal corresponding to the stretching of C–C bonds present in the hydrocarbon chains was noticed at 1097 cm −1 . Additionally, a very sharp peak observed at 722 cm −1 can be associated with the methylene group rocking vibration [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…In first phase, suitability of FT MIR and FT NIR spectroscopy in reflectance and transmittance mode for analysis of ghee was evaluated (Antony et al, 2016). In second phase, spectral characterization of cow and buffalo ghee in MIR region using reflectance mode (Antony et al, 2017) and in NIR region using transmittance mode (Antony et al, 2018a) was carried out. In final phase of the study attempts were made to develop IR spectroscopy based method for detection and quantification of foreign oils and fats mixed with ghee.…”
Section: Introductionmentioning
confidence: 99%